The Effect of Game Based Learning Model Assisted by Blooket Media on English Vocabulary Mastery of Elementary School Students - Dellisa Ahyani; Nadia Tiara Antik Sari; Alfiana Nurussama (Lembaga Bale Literasi, 2026)
This study aims to determine the effect of the Game Based Learning model assisted by Blooket media on the mastery of English vocabulary among fifth-grade students of SDN 2 Sindangkasih, Purwakarta Regency. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 54 students: class VA (27 students) as the experimental group and class VB (27 students) as the control group. Data were collected through pretest and posttest, analyzed using Shapiro-Wilk normality test, homogeneity test, independent sample t-test, N-Gain test, and simple linear regression with SPSS version 29. The results showed: (1) there is a significant effect of the Game Based Learning model assisted by Blooket media on students’ English vocabulary mastery with a coefficient of determination of 56.3%; (2) the improvement in vocabulary mastery in the experimental group (N-Gain 61.70%, medium category) was higher and significant compared to the control group (N-Gain 18.68%, low category) with sig. value 0.001 < 0.05. It is concluded that the Game Based Learning model assisted by Blooket media is effective in improving English vocabulary mastery among elementary school students.